2011
DOI: 10.1007/s00253-011-3132-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cold-active family VIII esterases from an arctic soil metagenome

Abstract: Functional screening for lipolytic enzymes at low temperatures resulted in the isolation of the novel cold-active esterases, EstM-N1 and EstM-N2, from a metagenomic DNA library of arctic soil samples. EstM-N1 and EstM-N2 were 395 and 407 amino acids in length, respectively, and showed the highest similarity to class C β-lactamases. However, they shared a relatively low level of sequence similarity (30%) with each other. Phylogenetic analysis of bacterial lipolytic enzymes confirmed that EstM-N1 and EstM-N2 bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…The discovery and characterization of carboxylesterases, including family VIII, have previously been reported in other metagenomic studies (12,19,26,33). A relationship between family VIII carboxylesterases and ␤-lactamase has often been proposed due to the presence of the S-X-X-K motif; however, no single enzyme has been demonstrated to have both esterase and ␤-lactamase activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery and characterization of carboxylesterases, including family VIII, have previously been reported in other metagenomic studies (12,19,26,33). A relationship between family VIII carboxylesterases and ␤-lactamase has often been proposed due to the presence of the S-X-X-K motif; however, no single enzyme has been demonstrated to have both esterase and ␤-lactamase activities.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between family VIII carboxylesterases and ␤-lactamase has often been proposed due to the presence of the S-X-X-K motif; however, no single enzyme has been demonstrated to have both esterase and ␤-lactamase activities. Recently, it has been reported that proteins of metagenomic origin belonging to family VIII carboxylesterases (26,33) could hydrolyze nitrocefin, which is a chromogenic substrate for assessing ␤-lactamase activity. However, none of these enzymes was able to hydrolyze ␤-lactam antibiotic substrates such as ampicillin, carbenicillin, cephalosporin C, or cephalothin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest characterised relative was EstM-N2 (49% amino acid identity), a metagenome derived cold-active esterase belonging to the family VIII esterase/lipase and class C β-lactamases [37]. Further sequence A c c e p t e d M a n u s c i analysis searches using the Lipase Engineering database [38] and the Arpigny and Jaeger classification scheme [5] indicated that EstG34 was a family VIII carboxylesterase.…”
Section: Resultsmentioning
confidence: 99%
“…3). 41,42 This group contains the Class C b-lactamases and a number of b-lactamase like proteins, though the exact function of many of these proteins has yet to be biochemically determined.…”
Section: Analysis Of the Abgt Genementioning
confidence: 99%